Agreement on arrangements between Iceland, the Principality of Liechtenstein, the Kingdom of Norway and the United Kingdom of Great Britain and Northern Ireland following the withdrawal of the United Kingdom from the European Union, the EEA Agreement and other agreements applicable between the United Kingdom and the EEA EFTA States by virtue of the United Kingdom's membership of the European Union, London, 28 January 2020. ([2020-01-29]) - Unknown
No abstract available